The Effects of Immigration Quotas on Wages, the Great Black Migration, and Industrial Development - Bin Xie (Institute of Labor Economics (IZA), 2017)
This paper exploits the exogenous and differential immigrant supply shocks caused by the immigration quota system in the 1920s to identify the causal effects of the immigration restriction on the US manufacturing wages, the Great Migration, and industrial production between 1920 and 1930. I find that the immigration restriction significantly increased manufacturing wages and encouraged the southern black population to migrate to the North. I also find that the decline in the immigrant supply constrained the growth of the scale of manufacturing production and discouraged technology adoption of electrification.
Keywords: J61; K37; N32; 330; immigration restriction; Great Black Migration; industrial development